The effectiveness and feasibility of an online educational program for improving evidence-based practice literacy: an exploratory randomized study of US chiropractors. Issue 1 (December 2016) - Schneider, Michael; Evans, Roni; Haas, Mitchell; Leach, Matthew; Delagran, Louise; Hawk, Cheryl; Long, Cynthia; Cramer, Gregory; Walters, Oakland; Vihstadt, Corrie; Terhorst, Lauren
Abstract Background Online education programs are becoming a popular means to disseminate knowledge about evidence-based practice (EBP) among healthcare practitioners. This mode of delivery also offers a viable and potentially sustainable solution for teaching consistent EBP content to learners over time and across multiple geographical locations. We conducted a study with 3 main aims: 1) develop an online distance-learning program about the principles of evidence-based practice (EBP) for chiropractic providers; 2) test the effectiveness of the online program on the attitudes, skills, and use of EBP in a sample of chiropractors; and 3) determine the feasibility of expanding the program for broader-scale implementation. This study was conducted from January 2013 to September 2014. Methods This was an exploratory randomized trial in which 293 chiropractors were allocated to either an online EBP education intervention or a waitlist control. The online EBP program consisted of 3 courses and 4 booster lessons, and was developed using educational resources created in previous EBP educational programs at 4 chiropractic institutions. Participants were surveyed using a validated EBP instrument (EBASE) with 3 rescaled (0 to 100) subscores: Attitudes, Skills, and Use of EBP. Multiple regression was used to compare groups, adjusting for personal and practice characteristics. Satisfaction and compliance with the program was evaluated to assess feasibility. Results The Training Group showed modest improvement compared to the Waitlist Group in attitudes (Δ =6.2, p < .001) and skills (Δ =10.0, p < .001) subscores, but not the use subscore (Δ = −2.3, p = .470). The majority of participants agreed that the educational program was 'relevant to their profession' (84 %) and 'was worthwhile' (82 %). Overall, engagement in the online program was less than optimal, with 48 % of the Training Group, and 42 % of the Waitlist Group completing all 3 of the program courses. Conclusions Online EBP training leads to modest improvements in chiropractors' EBP attitudes and skill, but not their use of EBP. This online program can be delivered to a wide national audience, but requires modification to enable greater individualization and peer-to-peer interaction. Our results indicate that it is feasible to deliver an online EBP education on a broad scale, but that this mode of education alone is not sufficient for making large changes in chiropractors' use of EBP.